Unifying Treatment of Notch Effects in Fatigue - NISHITANI, Hironobu; ENDO, Masahiro (Transactions of the Japan Society of Mechanical Engineers Series A, 1985)
According to the concept of "linear notch mechanics" proposed recently by one of authers, it is supposed that not only the crack initiation limit σw1 but also the crack propagation limit σw2 of a notched specimen can be evaluated unifyingly by the maximum elastic stress at the notch root σmax and the notch radius ρ alone. Some previous results concerning σw2 and the present experimental results concerning σw1 and σw2 support the above presumption.